Optical spectroscopy of charge transfer transitions in multiferroic manganites, ferrites, and related insulators (Review Article) - Moskvin, A.S.; Pisarev, R.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
We review results of theoretical and experimental studies of charge transfer (CT) transitions in multiferroic manganites, ferrites, and related insulators. Starting with a simple cluster model approach we address both onecenter p–d and two-center d–d CT transitions, their polarization properties, the role played by structural parameters, orbital mixing, and spin degree of freedom. We analyze optical ellipsometry data in the spectral range of 0.6–5.8 eV in perovskite and hexagonal rare-earth manganites RMnO3 and in orthorhombic manganites RMn2O5. We discuss two groups of iron oxides where Fe3+ ions occupy either only octahedral positions (BiFeO3, orhoferrites RFeO3 et al.) and materials with Fe3+ ions both in octahedral and tetrahedral positions(hematite α-Fe2O3, garnets RFe5O12, lithium ferrite LiFe5O8, Ca2Fe2O5 et al.).